PENGARUH CO-CREATION, CURRENCY, COMMUNAL ACTIVITY DAN CONVERSATION TERHADAP CONSUMER JOURNEY. - Devi Krisnawati (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
This research use descriptive research with quantitative approach. There are five variables that are used in this research: co-creation, currency, communal activity, conversation, and consumer journey. The collection of data obtained through online questionnaires, which were distributed randomly for six days. The sample in this research was 100 respondents. The sampling technique of this research is random sampling. The data analysis uses descriptive analysis and multiple linear regressions. The results in this research showed that co-creation, currency, communal activity, conversation simultaneously affecting consumer journey significantly. The other results showed that co-creation and conversation partially affecting consumer journey significantly. Otherwise, currency, and communal activity partially were not affecting consumer journey. Based on the result of this research, it’s better for a marketer or a company to maintain conversation and develop product with involvement of the customer to strengthen consumer journey.